Sheep Fattening as a Business and its Associated Challenges in the Tamale Metropolis, Ghana (Ghana Journal of Science, Technology and Development, 2023)
ABSTRACTThe study was carried out in the Tamale metropolis to assess sheep fattening as a business and its associated challenges. Fifty (50) farmers were selected randomly and questionnaire administered to them. Data were analyzed using SPSS. The study revealed that most (90%) of sheep fatteners in the metropolis were males. It also shows that majority (75%) had at least primary education and (24.7%) had no formal education. Majority (40%) of the farmers were within the age group 21-30 with the age group 51-60 years being the least. Most (80%) of the fatteners self-finance the business. Most of them fatten both sexes (90%) of animals and majority (66%) buy mature animals for fattening.  Most (73.5%) of the respondents fatten sheep for income generation, with other reasons being food security, prestige, and employment. The challenges they face in the industry include feed and water scarcity, diseases and mortality, theft/loss of animals and accidents. Price of sheep at sale was determined by bargaining through visual estimation of weight and condition scoring. Most of them sell their fattened sheep at home. It was therefore concluded that sheep fattening in the Tamale metropolis is small scale business. Farmers should be educated on general management and husbandry practices to help reduce production losses and to help them go in to large scale farming since their main aim is to get income.